TNF Neutralization Results in the Delay of Transplantable Tumor Growth and Reduced MDSC Accumulation - Atretkhany, Kamar-Sulu N.; Nosenko, Maxim A.; Gogoleva, Violetta S.; Zvartsev, Ruslan V.; Qin, Zhihai; Nedospasov, Sergei A.; Drutskaya, Marina S. (Frontiers in Immunology, 2016)
Myeloid-derived suppressor cells (MDSCs) represent a heterogeneous population of immature myeloid cells (IMCs) that, under normal conditions, may differentiate into mature macrophages, granulocytes, and dendritic cells. However, under pathological conditions associated with inflammation, cancer, or infection, such differentiation is inhibited leading to IMC expansion. Under the influence of inflammatory cytokines, these cells become MDSCs, acquire immunosuppressive phenotype, and accumulate in the affected tissue, as well as in the periphery. Immune suppressive activity of MDSCs is partly due to upregulation of arginase 1, inducible nitric oxide synthase, and anti-inflammatory cytokines, such as IL-10 and TGF-β. These suppressive factors can enhance tumor growth by repressing T-cell-mediated anti-tumor responses. TNF is a critical factor for the induction, expansion, and suppressive activity of MDSCs. In this study, we evaluated the effects of systemic TNF ablation on tumor-induced expansion of MDSCs in vivo using TNF humanized (hTNF KI) mice. Both etanercept and infliximab treatments resulted in a delayed growth of MCA 205 fibrosarcoma in hTNF KI mice, significantly reduced tumor volume, and also resulted in less accumulated MDSCs in the blood 3 weeks after tumor cell inoculation. Thus, our study uncovers anti-tumor effects of systemic TNF ablation in vivo.